Synthesis and characterization of branched polymers via anionic polymerization based on “strathclyde approach” / Shehu Habibu - Shehu , Habibu (2019)
Branched polymers continue to attract interest in recent years due to their favorable properties over their linear counterparts. This work aimed at developing a synthetic route towards highly branched polymers from commercially available raw materials, in good yield and devoid of microgelation, i.e., to prepare a completely soluble polymer.In particular, anionic polymerization technique has been utilized to synthesize highly branched polymers of isoprene. The polymerizations were conducted under high vacuum conditions using sec-butyllithium as initiator at 50 °C in toluene. Toluene served both as a solvent and as a chain transfer agent while tetramethylethylenediamine (TMEDA) served as the polar modifier with a commercial mixture of divinylbenzene (DVB) employed as the branching agent for the “living” poly(isoprenyl)lithium anions. The nature of the reaction was studied on the TMEDA/Li ratio as well as the DVB/Li ratio. The obtained branched polymers were characterized by triple detection size exclusion chromatography (SEC), nuclear magnetic resonance (NMR) spectroscopy, melt rheology, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and transmission electron microscopy (TEM). The characterizations in terms of structural, rheological, thermal and morphological properties carried out on the branched polymers are hereby described and compared with those of the linear polymers. Broad molecular weight distributions have been obtained for the highly branched polymer products. 1H NMR spectroscopy reveals the dominance of 3,4– polyisoprene microstructure. It was found that the complex viscosities and dynamic moduli of the branched samples were much lower compared to their linear counterparts. TEM studies show that the linear polyisoprene exhibited long-range order, which disappeared with increasing degree of branching. The branched polymers were thermally stable (up to ~ 387 °C) and completely soluble in common solvents. They decomposed via multistep reaction mechanism as manifested by the nonlinear relationship between the activation energy and the extent of conversion. The results also indicated that the trend of activation energy of the branched polymers studied increases with DVB content and decrease with increasing molecular weight distribution. The average Ea were found between 260.15–32031 kJmol-1and the results showed that the average values of Ea obtained by KAS (262.34 kJ mol-1 to 314.65 kJ mol-1) and FWO (260.15 kJ mol-1 to 309.67 kJ mol-1) methods were in agreement with those obtained from the Kissinger method (265.79 kJ mol-1 to 282.75 kJ mol-1). The results conform with earlier findings by the “Strathclyde team” for radical polymerization systems. This methodology has the potential of providing soluble branched vinyl polymers at low cost using the readily available raw materials.